Tanshinone IIA Restrains Hepatocellular Carcinoma Progression by Regulating METTL3-Mediated m6A Modification of TRIB3 mRNA - Jiang, Ying; Wang, Xinjie; Wang, Zhenyang; Zhang, Shengliang; Wang, Jianhua; Wang, Xianglong; Zhang, Yang (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Hepatocellular carcinoma (HCC) is a molecularly heterogeneous solid malignancy that carries a dismal prognosis. Tanshinone IIA (Tan-IIA) is involved in the regulation of N6-methyladenosine (m6A) modification and plays an anti-tumor role in HCC, but whether Tan-IIA regulates HCC by mediating m6A modification is unclear. Methods and Materials: Cell apoptosis, invasion, proliferation, viability, and stemness were estimated with flow cytometry, tran swell, 5-ethynyl-2’-deoxyuridine, 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide, and sphere-forming assays. Methyltransferase-like 14 (METTL14) and 3 (METTL3) mRNA and protein levels were detected with reverse transcription-quantitative polymerase chain reaction and western blotting. Total m6A levels were measured using an m6A RNA methylation quantification kit. A possible regulation of tribbles pseudokinase-3 (TRIB3) expression by METTL3 in an m6A-modified manner was predicted through RM2Target and SRAMP and verified by m6A methylated RNA immunoprecipitation (MeRIP) and RIP. Mouse xenograft models assessed the action of Tan-IIA in HCC tumorigenesis. Results: Tanshinone IIA restrained HCC cell viability, proliferation, invasion, and stemness, and induced HCC cell apoptosis invitro, as well as repressed tumor growth in xenograft models. METTL3 and TRIB3 were upregulated in HCC samples and downregulated in Tan IIA-treated HCC cells and xenograft tumors. METTL3 facilitated HCC cell viability, proliferation, invasion, and stemness by enhancing TRIB3 mRNA stability through m6A modification. Tan-IIA played its role by downregulating TRIB3, and Tan-IIA mediated TRIB3 expres sion by METTL3. Conclusion: Tanshinone IIA restrained HCC progression by regulating METTL3-mediated m6A modification of TRIB3 mRNA, offering evidence to support the clinical translation of Tan-IIA. Cite this article as: Jiang Y, Wang X, Wang Z, et al. Tanshinone IIA restrains hepatocellular carcinoma progression by regulating METTL3-mediated m6A modification of TRIB3 mRNA. Turk J Gastroenterol. 2025;36(7):431-441.